Proliferating cells in the adolescent rat amygdala: Characterization and response to stress. (17th December 2015) - Saul, M.L.; Helmreich, D.L.; Rehman, S.; Fudge, J.L.
Highlights: Approximately 25% of BrdU+ cells in adolescent amygdala contain DCX, and do not mature to a neural profile after 28 days. Approximately 50% of BrdU+ cells co-contain NG2, a marker of oligodendrocyte precursors. Stress reduces NG2/BrdU+ cells in the amygdala by 50%, while DCX/BrdU+ cells are unaffected. Stress-induced BrdU+ cell changes are likely not due to cell death, as measured by TUNEL labeling. Abstract: The amygdala is a heterogeneous group of nuclei that plays a role in emotional and social learning. As such, there has been increased interest in its development in adolescent animals, a period in which emotional/social learning increases dramatically. While many mechanisms of amygdala development have been studied, the role of cell proliferation during adolescence has received less attention. Using bromodeoxyuridine (BrdU) injections in adolescent and adult rats, we previously found an almost fivefold increase in BrdU-positive cells in the amygdala of adolescents compared to adults. Approximately one third of BrdU-labeled cells in the amygdala contained the putative neural marker doublecortin (DCX), suggesting a potential for neurogenesis. To further investigate this possibility in adolescents, we examined the proliferative dynamics of DCX/BrdU-labeled cells. Surprisingly, DCX/BrdU-positive cells were found to comprise a stable subpopulation of BrdU-containing cells across survivals up to 56 days, and there was no evidence of neural maturation by 28 days after BrdU injection. Additionally, we found that approximately 50% of BrdU+ cells within the adolescent amygdala contain neural-glial antigen (NG2) and are therefore presumptive oligodendrocyte precursors (OPCs). We next characterized the response to a short-lived stressor (3-day repeated variable stress, RVS). The total BrdU-labeled cell number decreased by ∼30% by 13 days following RVS (10 days post-BrdU injection) as assessed by stereologic counting methods, but the DCX/BrdU-labeled subpopulation was relatively resistant to RVS effects. In contrast, NG2/BrdU-labeled cells were strongly influenced by RVS. We conclude that typical neurogenesis is not a feature of the adolescent amygdala. These findings point to several possibilities, including the possibility that DCX/BrdU cells are late-developing neural precursors, or a unique subtype of NG2 cell that is relatively resistant to stress. In contrast, many proliferating OPCs are significantly impacted by a short-lived stressor, suggesting consequences for myelination in the developing amygdala.